Heart failure subtypes and thromboembolic risk in patients with atrial fibrillation: The PREFER in AF - HF substudy. (15th August 2018) - Siller-Matula, Jolanta M.; Pecen, Ladislav; Patti, Giuseppe; Lucerna, Markus; Kirchhof, Paulus; Lesiak, Maciej; Huber, Kurt; Verheugt, Freek W.A.; Lang, Irene M.; Renda, Giulia; Schnabel, Renate B.; Wachter, Rolf; et al.
Abstract: Background and objectives: To assess thromboembolic and bleeding risks in patients with heart failure (HF) and atrial fibrillation (AF) according to HF type. Methods: We analyzed 6170 AF patients from the Prevention of thromboembolic events - European Registry in Atrial Fibrillation (PREFER in AF), and categorized patients into: HF with reduced left-ventricular ejection fraction (HFrEF; LVEF < 40%); mid-range EF (HFmrEF; LVEF: 40–49%); lower preserved EF (HFLpEF; LVEF: 50–60%), higher preserved EF (HFHpEF; LVEF > 60%), and no HF. Outcomes were ischemic stroke, major adverse cardiovascular and cerebral events (MACCE) and major bleeding occurring within 1-year. Results: The annual incidence of stroke was linearly and inversely related to LVEF, increasing by 0.054% per each 1% of LVEF decrease (95% CI: 0.013%–0.096%; p = 0.031). Patients with HFHpEF had the highest CHA2 DS2 -VASc score, but significantly lower stroke incidence than other HF groups (0.65%, compared to HFLpEF 1.30%; HFmrEF 1.71%; HFrEF 1.75%; trend p = 0.014). The incidence of MACCE was also lower in HFHpEF (2.0%) compared to other HF groups (range: 3.8–4.4%; p = 0.001). Age, HF type, and NYHA class were independent predictors of thromboembolic events. Conversely, major bleeding did not significantly differ between groups ( p = 0.168). Conclusion: Our study in predominantly anticoagulated patients with AF shows that, reduction in LVEF is associated with higher thromboembolic, but not higher bleeding risk. HFHpEF is a distinct and puzzling group, featuring the highest CHA2 DS2 -VASc score but the lowest residual risk of thromboembolic events, which warrants further investigation. Highlights: The subtype of heart failure predicts thromboembolic events. NYHA class is a strong and independent predictor of thromboembolic events. HFLpEF and HFHpEF represent distinct populations, which differ in terms of thromboembolic risk. Mortality increases with decreasing EF, and was highest in HFrEF.